1954
DOI: 10.1080/17470215408416656
|View full text |Cite
|
Sign up to set email alerts
|

An Illusion of Movement Complementary to the Horizontal-Vertical Illusion

Abstract: Blindfolded subjects moved a stylus held in the hand over a standard distance of 4.5 ins. in a given direction. They then attempted to move the same distance in a direction at right angles to the first. Eight combinations of movements were investigated. The results reveal an illusion such that the extent of movements to left or right across the body is underestimated, while the extent of movements towards or away from the body in the mid-line is overestimated. The illusion applies to speed as well as extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 2 publications
3
18
0
Order By: Relevance
“…The specific relationship may be governed by the points of emphasis of particular experiments. In this regard, Reid (1954) has observed from introspective reports that under conditions that give rise to the haptic L illusion, the subjects attempt to keep the speed of movement constant while estimating the duration of movement. Thus, the apparently longer radial extent is presumably preempted by a judgment of greater elapsed time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific relationship may be governed by the points of emphasis of particular experiments. In this regard, Reid (1954) has observed from introspective reports that under conditions that give rise to the haptic L illusion, the subjects attempt to keep the speed of movement constant while estimating the duration of movement. Thus, the apparently longer radial extent is presumably preempted by a judgment of greater elapsed time.…”
Section: Resultsmentioning
confidence: 99%
“…Such an analysis was suggested by Brown (1846Brown ( /1964) and more recently by Reid (1954), who both argued but without supporting data that the slower the speed in traversing an extent, the greater the extent appears. Such a relationship in fact was demonstrated by Wapner, Weinberg, Click, and Rand (1967), who found that with passive movement of the limb, a relatively faster (slower) speed gives rise to an apparently shorter (longer) extent.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The spokes of the wheel indicate the radial directions, with the tangential directions orthogonal to them. In 1954, Reid first showed a bias in the perceived extent of arm movements ( [2]). Subsequently, it was shown that the direction of arm movement expressed in trunk-centered coordinates (radial vs. tangential) was fundamental to this bias ( [3,4]): arm movements executed in the radial direction were consistently overestimated, whereas tangential movements were underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these effects carry clear relationships to visual illusions, but some do not. Reid described the vertical-horizontal illusion occurring when gauging the length of identical objects at different orientation as analog to that in vision [63]. Davidon and Cheng reported that subjects consistently overestimated the lengths of objects when using a radial movement rather than a lateral one, but disputed analogy with visual effects [17].…”
Section: Kinaesthetic Effectsmentioning
confidence: 99%